If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + 2y) + 7y = 19 (1 * 3 + 2y * 3) + 7y = 19 (3 + 6y) + 7y = 19 Combine like terms: 6y + 7y = 13y 3 + 13y = 19 Solving 3 + 13y = 19 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 13y = 19 + -3 Combine like terms: 3 + -3 = 0 0 + 13y = 19 + -3 13y = 19 + -3 Combine like terms: 19 + -3 = 16 13y = 16 Divide each side by '13'. y = 1.230769231 Simplifying y = 1.230769231
| (-3*x+5)/(5-x^2)=11 | | 2.5x+-5/2x+12=12 | | 2.5x+-5/2x | | x+1=72/x | | 2(x-1)+3+-2x=7 | | showthat:sin(pi/4+4x)=sin(pi/3-2x) | | 1.00+3.00=3.00+2.00 | | x=r+4+4r-2 | | 2y-8=5x | | M^2-11=38 | | 0.5m=0.76 | | 15/72X9/45 | | 1l+854l-44k=365 | | 1x-12=-5 | | -12=-11+n/-12 | | 6x^6/x^2 | | 1/4x+3=2 | | n^2-n-1520=0 | | 2v+5=29 | | 6=2p+8 | | 15-12(-7x-6)= | | 30=-10+4m | | 12/3*9+20=x | | (t+6)(t-6)=(t+7)(t-8)+9 | | 12/3=x | | -3/8m+1+-13/8m=5 | | 2/5(4y+2x) | | 10-82/3 | | -185=-5-9b | | 10-8/3 | | 2=6+k/4 | | 2x^4-5x^3-16x+40=0 |